toner
The toner formulation with specific resin composition and wax content addresses abrasion resistance and backside staining issues by retaining wax on the image surface, ensuring high performance in various printing conditions.
Patent Information
- Application Number
- JP2021035002
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-05
- Publication Date
- 2024-12-23
- Estimated Expiration
- 2041-03-05
AI Technical Summary
Existing toners fail to provide adequate abrasion resistance and prevent backside staining on media, especially in low printing rate images, due to wax exuding from the image surface and reducing friction coefficient.
A toner formulation containing a binder resin with 30% amorphous polyester resin, a styrene-acrylic resin composition with a specific ratio of C=C bond to C-H bond absorption peak intensities, and 3-15 parts by mass of hydrocarbon wax, which enhances wax retention on the image surface.
The toner achieves improved hot offset resistance and charge retention under high temperature and humidity conditions, with enhanced abrasion resistance even in low printing rate images.
Smart Images

Figure 0007604272000001 
Figure 0007604272000002 
Figure 0007604272000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to toners for developing electrostatic images used in electrophotography, electrostatic recording, and the like. [Background technology]
[0002] In recent years, full-color electrophotographic copiers have become widespread and are beginning to be applied to the printing market, where there is a growing demand for high speed, high image quality, and high productivity while being compatible with a wide range of media (paper types). For example, even if the paper type is changed from thick paper to thin paper, there is a demand for media uniformity, which allows printing to continue without changing the process speed or the heating temperature setting of the fixing unit according to the paper type. From the viewpoint of media uniformity, a toner is required to complete fixing appropriately over a wide range of fixing temperatures, from low to high.
[0003] In order to fix the toner properly over a wide range of fixing temperatures, there is a method of improving hot offset resistance by adding wax to the toner to give the toner releasability. In this case, the dispersion state of the wax in the toner has a significant effect on the properties of the toner, so it is desirable for the wax to be finely and uniformly dispersed. However, even if the dispersion state of a toner containing wax is controlled, when the toner is left stationary under high temperature and high humidity conditions, the wax begins to dissolve on the toner surface, deteriorating the fluidity of the toner, and thus the charging property may be poor.
[0004] Therefore, as in Patent Document 1, a technology has been proposed in which a styrene-acrylic resin having a long-chain alkyl group is contained in the toner to control the state of the wax in the toner, thereby improving hot offset resistance and charge retention under high temperature and high humidity conditions. On the other hand, in the printing market, there is an increasing demand for the quality of the printed product. Depending on the media used, if the image surface of the media rubs against each other due to vibration during transportation of the printed matter, the toner image may be rubbed off, causing stains on the back of the media. Therefore, Patent Document 2 proposes a technique for improving the abrasion resistance of printed matter by controlling the amount of wax on the toner surface. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-116810 A [Patent Document 2] JP 2020-8818 A Summary of the Invention [Problem to be solved by the invention]
[0006] The abrasion resistance proposed in Patent Document 2 is achieved by lowering the coefficient of friction of the image surface due to the presence of wax that seeps out from the toner on the surface of the fixed image, and thus preventing the image from being rubbed off even when rubbed with a separation claw or the like. However, it has been found that in toners containing an amorphous polyester resin and a hydrocarbon wax, especially in images with a low printing rate, the friction resistance is reduced and back staining of the media may occur. This is thought to be because, in the case of images with a low printing rate, the area of the toner image is small, so the wax that seeps out onto the image surface during fixing cannot stay on the image surface and flows onto the media. As a result, the friction resistance of the image is reduced and back staining of the media may occur. Therefore, the toners disclosed in Patent Documents 1 and 2 may not be sufficient to prevent back staining of the media, and further improvement is needed. [Means for solving the problem]
[0007] The toner of the present disclosure is A toner having toner particles containing a binder resin, a hydrocarbon wax, and a styrene-acrylic resin composition, The binder resin contains 30% by mass or more of an amorphous polyester resin, The styrene-acrylic resin composition contains 4% by mass to 25% by mass of a unit represented by the following formula (1): The styrene-acrylic resin composition had an FT-IR spectrum measured by an ATR method under conditions of a Ge ATR crystal and an infrared light incidence angle of 45°. 1570cm due to the C=C bond of the aromatic ring -1 ~1630cm -1 The maximum absorption peak intensity in the range of A, 2800cm due to the C-H bond of hydrocarbons -1 ~2900cm -1 When the maximum absorption peak intensity in the range is B, The ratio (B / A) is 1.8 to 4.0, The toner is characterized in that it contains 3 parts by mass to 15 parts by mass of the hydrocarbon wax with respect to 100 parts by mass of the binder resin.
[0008] [ka] (In formula (1), n represents an integer of 10 to 36, and R represents H or CH3.) Effect of the Invention
[0009] According to the present disclosure, it is possible to provide a toner that has good hot offset resistance and charge retention under high temperature and high humidity conditions, and also has good abrasion resistance even in images with a low printing rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In this disclosure, the description of "xx or more and xx or less" or "xx to xx" indicating a numerical range is not intended to limit the scope of the present invention. Unless otherwise stated, the range refers to a numerical range including the endpoints, lower and upper limits. The present inventors have conducted extensive research with the aim of improving the abrasion resistance of images with a low printing ratio. As a result, they have found that by using the toner described below, an unprecedentedly excellent abrasion resistance can be obtained even in images with a low printing ratio. That is, the toner of the present disclosure is A toner having toner particles containing a binder resin, a hydrocarbon wax, and a styrene-acrylic resin composition, The binder resin contains 30% by mass or more of an amorphous polyester resin, The styrene-acrylic resin composition contains 4% by mass to 25% by mass of a unit represented by the following formula (1): The styrene-acrylic resin composition had an FT-IR spectrum measured by an ATR method under conditions of a Ge ATR crystal and an infrared light incidence angle of 45°. 1570cm due to the C=C bond of the aromatic ring -1 ~1630cm -1 The maximum absorption peak intensity in the range of A, 2800cm due to the C-H bond of hydrocarbons -1 ~2900cm -1 When the maximum absorption peak intensity in the range is B, The ratio (B / A) is 1.8 to 4.0, The toner is characterized in that it contains 3 parts by mass to 15 parts by mass of the hydrocarbon wax with respect to 100 parts by mass of the binder resin.
[0011] [ka] (In formula (1), n represents an integer of 10 to 36, and R represents H or CH3.)
[0012] The present inventors believe that the reason why the effects of the present disclosure are achieved is as follows. The main reason that abrasion resistance deteriorates in images with low printing rates is that, as described above, the hydrocarbon wax that seeps out during fixing cannot remain on the image surface and flows onto the media, increasing the friction coefficient of the image surface. The reason why the hydrocarbon wax cannot remain on the image surface is that the amorphous polyester resin contained as the binder resin and the hydrocarbon wax contained as the release agent have different polarities. The hydrocarbon wax contained in the toner seeps out onto the image surface during fixing and functions as a release agent, improving hot offset resistance.
[0013] However, due to the difference in polarity, the exuded hydrocarbon wax does not have enough energy to remain on the image surface, and as a result, in images with low printing ratios, the amount of wax on the image surface decreases as the hydrocarbon wax flows from the image surface to the media, resulting in poor abrasion resistance. Therefore, in order to improve the abrasion resistance, even in the case of an image with a low printing ratio, it is necessary to keep the wax that has exuded onto the image surface during fixing on the image surface.
[0014] The present inventors have discovered that in a toner containing a polyester resin, a hydrocarbon wax, and a specific styrene-acrylic resin composition, the styrene-acrylic resin composition exerts an effect of retaining the hydrocarbon wax on the image surface during fixing, and have arrived at the present disclosure. The styrene-acrylic resin composition according to the present disclosure contains 4% by mass to 25% by mass of a unit represented by the following formula (1): In the FT-IR spectrum obtained by measuring using the ATR method with Ge (germanium) as the ATR crystal and an infrared light incidence angle of 45°, 1570cm due to the C=C bond of the aromatic ring -1 ~1630cm -1 The maximum absorption peak intensity in the range of A, 2800cm due to the C-H bond of hydrocarbons -1 ~2900cm -1 When the maximum absorption peak intensity in the range is B, It is characterized by a ratio (B / A) of 1.8 to 4.0.
[0015] [ka] (In formula (1), n represents an integer of 10 to 36, and R represents H or CH3.)
[0016] The styrene-acrylic resin composition is characterized by containing a unit represented by formula (1). The unit represented by formula (1) has a hydrocarbon group in which n is 10 to 36, and therefore has improved affinity with hydrocarbon wax, and an effect of retaining the hydrocarbon wax on the image surface is obtained. Examples of the unit represented by formula (1) in which n is 10 to 36 include units derived from the following monomers. Examples of the acrylates include lauryl acrylate, lauryl methacrylate, stearyl acrylate, stearyl methacrylate, nonadecyl acrylate, nonadecyl methacrylate, eicosyl acrylate, eicosyl methacrylate, heneicosanyl acrylate, heneicosanyl methacrylate, behenyl acrylate, behenyl methacrylate, lignoceryl acrylate, lignoceryl methacrylate, ceryl acrylate, ceryl methacrylate, octacosa acrylate, octacosa methacrylate, myrisyl acrylate, myrisyl methacrylate, dodoriaconta acrylate, and dodoriaconta methacrylate.
[0017] In the formula (1), n is preferably 12 to 30, more preferably 18 to 22, and further preferably 22. That is, structures derived from behenyl acrylate and behenyl methacrylate are preferred. When the carbon number represented by n is within the above range, the affinity with the hydrocarbon wax is improved and the effect of retaining the hydrocarbon wax on the image surface is enhanced, thereby improving abrasion resistance.
[0018] By including the unit of formula (1) in the styrene-acrylic resin composition in an amount of 4% by mass to 25% by mass, the unit is likely to bleed out with the hydrocarbon wax during fixing. Moreover, the unit is present at the interface between the polyester resin and the hydrocarbon wax, allowing the hydrocarbon wax to remain on the image surface, resulting in good abrasion resistance and hot offset resistance. The content of the unit of formula (1) is preferably from 4% by mass to 20% by mass, more preferably from 4% by mass to 15% by mass.
[0019] In the FT-IR spectrum of the styrene-acrylic resin composition, -1 ~1630cm -1 The maximum absorption peak intensity A in the range is a peak derived from the C=C bond of the aromatic ring, and is a peak derived from a styrene unit. On the other hand, in the FT-IR spectrum of the styrene-acrylic resin composition, -1 ~2900cm -1 The maximum absorption peak intensity B in the range is a peak derived from a C-H bond of a hydrocarbon. Since a C-H bond exists in the unit represented by the above formula (1) and also exists in multiple locations in the styrene-acrylic resin composition, the peak derived from a C-H bond is a combined peak.
[0020] That is, the ratio (B / A) of maximum absorption peak intensities A and B indicates the ratio of hydrocarbon units to styrene units in the styrene-acrylic resin composition. When the ratio of the hydrocarbon unit to the styrene unit (B / A) is 1.8 to 4.0, the styrene-acrylic resin composition can obtain the following effects of enhancing molecular mobility and affinity. · Molecular mobility required for permeation onto the image surface during fixing. - By being present at the interface between polyester resin and hydrocarbon wax, it has the effect of increasing the affinity with the hydrocarbon wax.
[0021] The hydrocarbon unit in the styrene acrylic resin composition is necessary to increase the affinity with the hydrocarbon wax, but has high molecular mobility. If the molecular mobility is too high, the styrene acrylic resin composition will not remain on the image surface when it seeps out during fixing, and will flow into the media together with the hydrocarbon wax, so that the effect of improving the abrasion resistance cannot be obtained. Furthermore, a styrene acrylic resin composition with high molecular mobility functions as a leak site for charging in a toner. If a styrene acrylic resin composition with high molecular mobility is contained under high temperature and high humidity conditions, there is a risk that the charge retention will deteriorate.
[0022] On the one hand, the styrene unit can achieve the effect of suppressing the molecular mobility of the styrene-acrylic resin composition. Therefore, by controlling the molecular mobility with the styrene unit, it becomes easier to stay on the image surface, the abrasion resistance is improved, and the charge retention property is good. That is, it is necessary to enhance the affinity with the hydrocarbon wax with the hydrocarbon unit and control the molecular mobility with the styrene unit. By setting the ratio (B / A) of them to be 1.8 - 4.0, the abrasion resistance and the charge retention property are improved. The ratio (B / A) of the hydrocarbon unit to the styrene unit is more preferably 2.0 - 3.5, and even more preferably 2.0 - 3.0. By being within the above range, the affinity with the hydrocarbon wax and the molecular mobility become better, and the abrasion resistance and the charge retention property are good.
[0023] <Measurement of FT-IR Spectrum by ATR Method> The measurement of the FT-IR spectrum by the ATR method was performed using the following apparatus. · Fourier transform infrared spectrometer (trade name: Spectrum One, manufactured by PerkinElmer) equipped with a Universal ATR Sampling Accessory (universal ATR measurement accessory) The incident angle of the infrared light was set to 45°. As the prism used for the ATR measurement, a Ge ATR crystal (refractive index = 4.0) was used.
[0024] Other measurement conditions are as follows. Range Start: 4000 cm -1 End: 600 cm -1 (Ge ATR crystal) Duration Scan number: 4 Resolution: 4.00 cm -1 Advanced: With CO2 / H2O correction
[0025] The specific measurement procedure is as follows. How to calculate the ratio (B / A) (1) A Ge ATR crystal (refractive index = 4.0) is attached to the device. (2) Set the Scan type to Background and Units to EGY and measure the background. (3) Set Scan type to Sample and Units to A. (4) Accurately weigh out 0.01 g of the sample onto the ATR crystal. (5) Pressurize the sample with the pressure arm (Force Gauge is 100).
[0026] (6) Measure the sample. (7) The obtained FT-IR spectrum is baseline corrected using Automatic Correction. (8) 1,570 cm -1 ~1630cm -1 Calculate the maximum absorption peak intensity in the range of (A). (9) 2,800 cm -1 ~2900cm -1 Calculate the maximum absorption peak intensity in the range of (B). (10) Calculate the ratio (B / A).
[0027] The toner is characterized in that it contains 3 parts by mass to 15 parts by mass of hydrocarbon wax per 100 parts by mass of binder resin. Hydrocarbon wax is a material with a low friction coefficient, so it is necessary for improving friction resistance, and also serves as a release agent to improve hot offset resistance. The toner of the present disclosure contains 3 parts by mass to 15 parts by mass of hydrocarbon wax per 100 parts by mass of binder resin, thereby improving friction resistance and hot offset resistance. The content of the hydrocarbon wax is more preferably 5 parts by mass to 10 parts by mass in order to obtain the above effects.
[0028] Examples of the hydrocarbon wax include low molecular weight polyethylene, low molecular weight polypropylene, olefin copolymer, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax. Among these, paraffin wax and Fischer-Tropsch wax are preferred because they have good abrasion resistance.
[0029] The styrene-acrylic resin composition is preferably a graft polymer having a hydrocarbon compound as the trunk portion and a styrene-acrylic resin as the branch portion, which improves the affinity with the hydrocarbon wax, enhances the effect of retaining the hydrocarbon wax on the image surface, and improves the hot offset resistance and abrasion resistance.
[0030] The hydrocarbon compound is preferably a polyolefin. By using a polyolefin, the reactivity of the graft polymerization between the hydrocarbon compound and the styrene-acrylic resin becomes good, and it becomes easier to obtain a more uniform styrene-acrylic resin composition. As a result, the effect of controlling molecular mobility by the styrene unit while increasing the affinity with the hydrocarbon wax is improved, the effect of retaining the hydrocarbon wax on the image surface is enhanced, and the hot offset resistance and abrasion resistance are improved. The method for graft modification is not particularly limited, and any method known in the art can be used.
[0031] The styrene-acrylic resin composition preferably contains 10% by mass to 30% by mass, more preferably 10% by mass to 20% by mass of the hydrocarbon compound unit. When the content is within the above range, the styrene-acrylic resin composition is likely to bleed out onto the image surface together with the hydrocarbon wax during fixing, and the effect of retaining the hydrocarbon wax on the image surface is enhanced, thereby improving the abrasion resistance.
[0032] The hydrocarbon compound unit is preferably at least one selected from the group consisting of polyethylene, polypropylene, alkylene copolymer, microcrystalline wax, paraffin wax, and hydrocarbon wax such as Fischer-Tropsch wax. Among them, polyethylene and polypropylene are preferred, and polypropylene is more preferred from the viewpoint of charge retention because it can suppress the molecular mobility of the hydrocarbon unit.
[0033] The styrene-acrylic resin composition may be a copolymer containing the unit represented by formula (1) and the styrene unit together with other monomers. The styrene-acrylic resin composition preferably contains 50% by mass or more of the styrene unit, more preferably 60% by mass or more. By setting the content within the above range, the molecular mobility of the styrene-acrylic resin composition is suppressed, and the charge retention is improved.
[0034] Examples of monomers that form styrene units include the following: styrene-based monomers such as styrene, α-methylstyrene, p-methylstyrene, m-methylstyrene, p-methoxystyrene, p-hydroxystyrene, p-acetoxystyrene, vinyltoluene, ethylstyrene, phenylstyrene, and benzylstyrene. Examples of other monomers include the following: vinyl ester monomers such as vinyl acetate, vinyl ether monomers such as vinyl methyl ether, halogen-containing vinyl monomers such as vinyl chloride, diene monomers such as butadiene and isobutylene, cycloalkyl-containing vinyl monomers such as cyclohexyl acrylate, and monomers that add acid values, such as acrylic acid, methacrylic acid, maleic anhydride, and maleic acid half ester, and combinations of these.
[0035] The acid value of the styrene-acrylic resin composition is preferably from 10.0 mgKOH / g to 30.0 mgKOH / g, and more preferably from 15.0 mgKOH / g to 30.0 mgKOH / g. When the acid value is within the above range, the charge retention is good, and the dispersibility of the styrene-acrylic resin composition in the amorphous polyester resin is good. The acid value can be controlled by adjusting the content of the monomer that imparts the acid value. The acid value is the number of milligrams of potassium hydroxide required to neutralize the acid contained in 1 g of the sample. The acid value of the resin is measured in accordance with JIS K0070-1992.
[0036] The weight average molecular weight of the styrene-acrylic resin composition is 1.5×10 4 ~1.0×10 5 It is preferable that the number of 4 ~5.0×10 4 By having the weight average molecular weight within the above range, the toner has good dispersibility in the polyester resin and is easily exuded to the image surface during fixing, resulting in good abrasion resistance.
[0037] <Measurement of weight average molecular weight> The weight average molecular weight of the styrene-acrylic resin composition is measured by gel permeation chromatography (GPC) as follows. First, a sample is placed in tetrahydrofuran (THF) and allowed to stand at 25°C for several hours, after which it is thoroughly shaken to mix well with the THF, and allowed to stand for a further 12 hours or more until no more of the sample remains. The solution is left to stand in THF for 24 hours. The resulting solution is then passed through a sample treatment filter (pore size 0.2 μm to 0.5 μm, for example, Myshoridisc H-25-2 (manufactured by Tosoh Corporation)) to prepare a GPC sample.
[0038] The sample concentration is adjusted to 0.5 mg / mL to 5.0 mg / mL. Using this sample solution, measurements are performed under the following conditions. The column is stabilized in a heat chamber at 40° C., and tetrahydrofuran (THF) is passed through the column at this temperature as a solvent at a flow rate of 1 mL per minute, and about 100 μL of the sample solution is injected and measured.
[0039] The columns are made by combining multiple commercially available polystyrene gel columns. A combination of Showa Denko's Shodex GPC KF-801, 802, 803, 804, 805, 806, 807, and 800P, or Tosoh Corporation's TSKgel G1000H(H XL ), G2000H(H XL ), G3000H(H XL ), G4000H(H XL ), G5000H(H XL ), G6000H(H XL ), G7000H(H XL ), a combination of TSKguard column is used.
[0040] In measuring the molecular weight of a sample, the molecular weight distribution of the sample is calculated from the relationship between the logarithm of a calibration curve prepared using several types of monodisperse polystyrene standard samples and the count value. The standard polystyrene samples used to create the calibration curve were those manufactured by Tosoh Corporation or Showa Denko Co., Ltd., with a molecular weight of 1 × 10 2 ~1×10 7 At least 10 standard polystyrene samples should be used. An RI (refractive index) detector should be used.
[0041] The toner of the present disclosure is characterized in that the binder resin contains 30% by mass or more of an amorphous polyester resin, preferably 50% by mass or more, and more preferably 70% by mass or more. When the content of the amorphous polyester resin is within the above range, the hydrocarbon wax on the fixed image is easily controlled from the viewpoint of affinity with the binder resin, the hydrocarbon wax, and the styrene-acrylic resin composition, and the friction resistance is improved and the hot offset resistance is also good.
[0042] In the present disclosure, the binder resin may be used in combination with other resins so long as the content of the amorphous polyester resin is within the above range. As the other resin, known binder resins can be used. For example, the following binder resins can be used. Styrene-based resins, styrene-based copolymer resins, polyol resins, polyvinyl chloride resins, phenolic resins, natural resin-modified phenolic resins, natural resin-modified maleic acid resins, acrylic resins, methacrylic resins, polyvinyl acetate, silicone resins, polyurethane resins, polyamide resins, furan resins, epoxy resins, xylene resins, polyvinyl butyral, terpene resins, coumarone-indene resins, and petroleum-based resins. Examples of resins that can be preferably used include styrene copolymer resins, polyester resins, and hybrid resins in which a polyester resin and a styrene copolymer resin are mixed or in which both are partially reacted.
[0043] The toner particles according to the present disclosure may contain a crystalline polyester resin. As the crystalline polyester resin, a known resin can be used. The components constituting the amorphous polyester resin will be described in detail below. The following components may be used singly or in combination depending on the type and application. Examples of the divalent acid component constituting the amorphous polyester resin include the following dicarboxylic acids or derivatives thereof.
[0044] benzenedicarboxylic acids such as phthalic acid, terephthalic acid, isophthalic acid, and phthalic anhydride, or their anhydrides or lower alkyl esters; alkyldicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and azelaic acid, or their anhydrides or lower alkyl esters; alkenylsuccinic acids or alkylsuccinic acids having an average carbon number of 1 to 50, or their anhydrides or lower alkyl esters; unsaturated dicarboxylic acids such as fumaric acid, maleic acid, citraconic acid, and itaconic acid, or their anhydrides or lower alkyl esters. The alkyl group in the lower alkyl esters includes a methyl group, an ethyl group, a propyl group, and an isopropyl group.
[0045] On the other hand, examples of the dihydric alcohol component constituting the amorphous polyester resin include the following. Ethylene glycol, polyethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-methyl-1,3-propanediol, 2-ethyl-1,3-hexanediol, 1,4-cyclohexanedimethanol (CHDM), hydrogenated bisphenol A, bisphenol and its derivatives represented by formula (I-1): and diols represented by formula (I-2).
[0046] [ka] In the formula (I-1), R represents an ethylene group or a propylene group, and x and y each represent an integer of 0 or more, and the average value of x+y is 0-10.
[0047] [ka] In the formula (I-2), R′ represents an ethylene group or a propylene group; x′ and y′ each represent an integer of 0 or more; and the average value of x′+y′ is 0-10. The components of the amorphous polyester resin may contain, in addition to the above-mentioned divalent carboxylic acid compound and divalent alcohol compound, a trivalent or higher carboxylic acid compound and a trivalent or higher alcohol compound as components.
[0048] The trivalent or higher carboxylic acid compound is not particularly limited, but examples thereof include trimellitic acid, trimellitic anhydride, and pyromellitic acid. Examples of the trihydric or higher alcohol compounds include trimethylolpropane, pentaerythritol, and glycerin. The components of the amorphous polyester resin may contain, in addition to the above-mentioned compounds, a monovalent carboxylic acid compound and a monovalent alcohol compound as components.Specifically, the monovalent carboxylic acid compound may include palmitic acid, stearic acid, arachidic acid, behenic acid, etc.In addition, cerotic acid, heptacosanoic acid, montanic acid, melissic acid, lacteric acid, tetracontanoic acid, pentacontanoic acid, etc. may also be mentioned.
[0049] Examples of the monohydric alcohol compounds include behenyl alcohol, ceryl alcohol, melissyl alcohol, and tetracontanol. The method for producing the amorphous polyester resin is not particularly limited, and any known method can be used. For example, the above-mentioned divalent carboxylic acid compound and divalent alcohol compound may be polymerized through an esterification reaction or an ester exchange reaction, and a condensation reaction to produce an amorphous polyester resin.
[0050] The polymerization temperature is not particularly limited, but is preferably in the range of 180°C to 290°C. In polymerizing the amorphous polyester resin, for example, a polymerization catalyst such as a titanium-based catalyst, a tin-based catalyst, zinc acetate, antimony trioxide, or germanium dioxide can be used. The softening point (hereinafter also simply referred to as Tm) of the binder resin in the present disclosure is preferably 85°C to 150°C, and more preferably 100°C to 150°C. When the softening point of the binder resin is within the above range, the hot offset resistance is improved. The glass transition temperature (Tg) of the binder resin is preferably from 50°C to 65°C, and more preferably from 55°C to 60°C. When the glass transition temperature (Tg) of the binder resin is within the above range, the charge retention of the toner is good.
[0051] <Measurement of glass transition temperature (Tg) of binder resin> The glass transition temperature of the binder resin is measured using a differential scanning calorimeter "Q1000" (manufactured by TA Instruments) in accordance with ASTM D3418-82. The melting points of indium and zinc are used for temperature correction of the device detection section, and the heat of fusion of indium is used for heat correction. Specifically, 5 mg of the resin composition is weighed out and placed in a silver pan. An empty silver pan is used as a reference, and the measurement is performed in the measurement range of 30° C. to 180° C. at a temperature increase rate of 10° C. / min.
[0052] The temperature is first raised to 180°C and held there for 10 minutes, then lowered to 30°C, and then raised again. During this second heating process, a specific heat change is obtained in the range of 30°C to 180°C. The glass transition temperature (Tg:°C) of the resin is determined as the temperature at the point where a straight line equidistant in the vertical direction from a straight line extending the baseline before and after the specific heat change occurs intersects with the curve of the stepwise change in the glass transition in the DSC curve.
[0053] <Measurement of the softening point (Tm) of the binder resin> In the present disclosure, the softening point (Tm) of a resin can be measured using a constant load extrusion type capillary rheometer "Flow characteristic evaluation device Flow Tester CFT-500D" (manufactured by Shimadzu Corporation). The CFT-500D is an instrument that applies a constant load from above using a piston while heating and melting the measurement sample filled in a cylinder and pushing it out through a capillary hole at the bottom of the cylinder, and can graph a flow curve from the amount of descent of the piston (mm) and the temperature (℃) during this process.
[0054] In the present disclosure, the "melting temperature in the 1 / 2 method" described in the manual attached to the "flow property evaluation device, flow tester CFT-500D" is defined as the softening point (Tm). The melting temperature in the 1 / 2 method is calculated as follows.
[0055] First, calculate half the difference between the amount of piston descent when the outflow ends (end of outflow, Smax) and the amount of piston descent when the outflow starts (minimum point, Smin) (this is X; X=(Smax-Smin) / 2). Then, the temperature on the flow curve when the amount of piston descent is the sum of X and Smin is the melting temperature in the 1 / 2 method. The measurement sample is prepared by compressing 1.2 g of resin at 10 MPa for 60 seconds using a tablet press (e.g., a standard manual Newton press NT-100H, manufactured by NPA Systems) in an environment of 25°C to form a cylindrical shape with a diameter of 8 mm.
[0056] The specific operations for the measurement are performed according to the manual that comes with the device. The measurement conditions for the CFT-500D are as follows. Test mode: Temperature rise method Starting temperature: 40℃ Achieved temperature: 200℃ Measurement interval: 1.0℃ Heating rate: 4.0℃ / min Piston cross-sectional area: 1.000cm 2 Test load (piston load): 5.0kgf Preheat time: 300 seconds Die hole diameter: 1.0mm Die length: 1.0mm
[0057] The toner of the present disclosure can be used as any of a magnetic one-component toner, a non-magnetic one-component toner, and a non-magnetic two-component toner. When used as a magnetic one-component toner, magnetic iron oxide particles are preferably used as the colorant. The magnetic iron oxide particles contained in the magnetic one-component toner include the following: magnetic iron oxides such as magnetite, maghemite, and ferrite, and magnetic iron oxides containing other metal oxides; metals such as Fe, Co, and Ni, or alloys of these metals with metals such as Al, Co, Cu, Pb, Mg, Ni, Sn, Zn, Sb, Be, Bi, Cd, Ca, Mn, Se, Ti, W, and V, and mixtures thereof.
[0058] The content of the magnetic iron oxide particles is preferably 30 parts by mass to 150 parts by mass or less with respect to 100 parts by mass of the binder resin. Examples of colorants for use in non-magnetic one-component toners and non-magnetic two-component toners include the following. As black pigments, carbon blacks such as furnace black, channel black, acetylene black, thermal black, and lamp black are used, and magnetic powders such as magnetite and ferrite are also used.
[0059] As a colorant suitable for yellow color, a pigment or a dye can be used. Pigments include the following: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 17, 23, 62, 65, 73, 74, 81, 83, 93, 94, 95, 97, 98, 109, 110, 111, 117, 120, 127, 128, 129, 137, 138, 139, 147, 151, 154, 155, 167, 168, 173, 174, 176, 180, 181, 183, 191, CI Vat Yellow 1, 3, 20. Examples of dyes include CI Solvent Yellow 19, 44, 77, 79, 81, 82, 93, 98, 103, 104, 112, and 162. These may be used alone or in combination of two or more.
[0060] As a colorant suitable for cyan, a pigment or a dye can be used. Examples of pigments include CI Pigment Blue 1, 7, 15, 15;1, 15;2, 15;3, 15;4, 16, 17, 60, 62, 66, etc., CI Vat Blue 6, and CI Acid Blue 45. Examples of dyes include CI Solvent Blue 25, 36, 60, 70, 93, 95, etc. These can be used alone or in combination of two or more.
[0061] As a colorant suitable for magenta, a pigment or a dye can be used. Examples of pigments include the following: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48, 48; 2, 48; 3, 48; 4, 49, 50, 51, 52, 53, 54, 55, 57, 57; 1, 58, 60, 63, 64, 68, 81, 81;1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 144, 146, 150, 163, 166, 169, 177, 184, 185, 202, 206, 207, 209, 220, 221, 238, 254, etc., CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35. Dyes for magenta include the following: Solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 52, 58, 63, 81, 82, 83, 84, 100, 109, 111, 121, 122, CI Disperse Red 9, CI Solvent Violet 8, 13, 14, 21, 27, CI Disperse Violet 1, basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40, CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28, etc. These can be used alone or in combination of two or more. The content of the colorant is preferably 1 part by mass to 20 parts by mass with respect to 100 parts by mass of the binder resin.
[0062] In order to impart releasability to the toner, waxes other than hydrocarbon waxes may be used in combination. Examples of waxes that can be used in the present disclosure include the following: oxidized waxes of aliphatic hydrocarbon waxes such as oxidized polyethylene wax; waxes mainly composed of fatty acid esters such as carnauba wax, behenyl behenate, and montan acid ester wax; and waxes in which fatty acid esters have been partially or completely deoxidized, such as deoxidized carnauba wax. In addition, the following may be used. Saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and valinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; saturated fatty acid bisamides such as methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, and hexamethylene bisstearic acid amide; ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, N unsaturated fatty acid amides such as N,N'-dioleyl adipamide, N,N'-dioleyl sebacamide; aromatic bisamides such as m-xylene bisstearamide, N,N'-distearyl isophthalamide; fatty metal salts such as calcium stearate, calcium laurate, zinc stearate, magnesium stearate (commonly known as metal soaps); waxes grafted onto aliphatic hydrocarbon waxes using vinyl copolymer monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols such as behenic acid monoglyceride; methyl ester compounds having hydroxy groups obtained by hydrogenation of vegetable oils and fats. The wax may be added during the production of the toner or during the production of the binder resin.
[0063] In the toner of the present disclosure, when the content of the styrene acrylic resin composition in the toner is X (mass%) and the content of the hydrocarbon wax is Y (mass%), the ratio (X / Y) is preferably 0.8 to 1.5, and more preferably 1.0 to 1.3. By setting the ratio (X / Y) within the above range, the affinity of the binder resin, the hydrocarbon wax, and the styrene-acrylic resin composition is well balanced, and the hydrocarbon wax is easily exuded and easily retained on the image surface during fixing, resulting in good hot offset resistance and abrasion resistance.
[0064] The toner of the present disclosure can use a known charge control agent as the charge control agent. Examples of known charge control agents include the following: azo iron compounds, azo chromium compounds, azo manganese compounds, azo cobalt compounds, azo zirconium compounds, chromium compounds of carboxylic acid derivatives, zinc compounds of carboxylic acid derivatives, aluminum compounds of carboxylic acid derivatives, and zirconium compounds of carboxylic acid derivatives. The carboxylic acid derivative is preferably an aromatic hydroxycarboxylic acid. A charge control resin can also be used. One or more types of charge control agents may be used in combination as necessary. It is preferable to add 0.1 to 10 parts by mass of the charge control agent to 100 parts by mass of the binder resin.
[0065] The toner of the present disclosure may be mixed with a magnetic carrier to be used as a two-component developer. As the magnetic carrier, a magnetic carrier such as a normal ferrite or magnetite, or a resin-coated carrier may be used. In addition, a binder-type magnetic carrier core in which a magnetic powder is dispersed in a resin may also be used.
[0066] Resin-coated carriers consist of magnetic carrier core particles and a resin coating layer that coats the surface of the magnetic carrier core particles. Examples of resins used in the resin coating layer include the following: styrene-acrylic resins such as styrene-acrylic acid ester copolymers and styrene-methacrylic acid ester copolymers; acrylic resins such as acrylic acid ester copolymers and methacrylic acid ester copolymers; fluorine-containing resins such as polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymers, monochlorotrifluoroethylene polymers, and polyvinylidene fluoride; silicone resins; polyester resins; polyamide resins; polyvinyl butyral; and aminoacrylate resins. Other examples include ionomer resins and polyphenylene sulfide resins. These resins can be used alone or in combination.
[0067] In the toner of the present disclosure, it is preferable to externally add silica fine powder to the toner particles in order to improve the charging stability, developing property, fluidity, and durability. The silica fine powder has a specific surface area of 30 m2 or less as measured by the BET method using nitrogen adsorption. 2 / g~500m 2 / g, and 50m 2 / g~400m 2 / g. Furthermore, the silica fine powder is preferably used in an amount of 0.01 to 8.00 parts by mass, and more preferably 0.10 to 5.00 parts by mass, per 100 parts by mass of toner particles.
[0068] The BET specific surface area of the silica fine powder can be calculated, for example, by adsorbing nitrogen gas onto the surface of the silica fine powder using a specific surface area measuring device described below and then using the BET multipoint method. Specific surface area measuring device: Autosorb 1 (product name, manufactured by Yuasa Ionics Co., Ltd.), GEMINI 2360 / 2375 (product name, manufactured by Micrometilix Co., Ltd.), Tristar 3000 (product name, manufactured by Micrometilix Co., Ltd.) If necessary, the silica fine powder is preferably treated with the following treating agents or a combination of various treating agents for the purpose of hydrophobizing and controlling triboelectric charging. Treatment agents: unmodified silicone varnish, various modified silicone varnishes, unmodified silicone oil, various modified silicone oils, silane coupling agents, silane compounds with functional groups, or other organosilicon compounds
[0069] Further, other external additives may be added to the toner of the present disclosure as necessary. Examples of such external additives include resin fine particles and inorganic fine powders that act as charge adjuvants, conductivity imparting agents, fluidity imparting agents, caking prevention agents, release agents during heat roller fixing, lubricants, abrasives, etc. Examples of charge adjuvants include metal oxides such as titanium oxide, zinc oxide, and alumina. Examples of lubricants include polyethylene fluoride powder, zinc stearate powder, and polyvinylidene fluoride powder. Examples of abrasives include cerium oxide powder, silicon carbide powder, and strontium titanate powder.
[0070] The method for producing the toner particles is not particularly limited, and may be any known method, such as a pulverization method, an emulsion aggregation method, a suspension polymerization method, or a dissolution suspension method. Toner particles produced by the pulverization method are produced, for example, as follows. A binder resin, a colorant, and other additives, if necessary, are thoroughly mixed using a mixer such as a Henschel mixer or a ball mill. The mixture is melt-kneaded using a thermal kneader such as a twin-screw kneading extruder, a heating roll, a kneader, or an extruder. At this time, wax, magnetic iron oxide particles, and a metal-containing compound can also be added. The melt-kneaded product is cooled and solidified, and then pulverized and classified to obtain toner particles. At this time, the average circularity of the toner particles can be controlled by adjusting the exhaust temperature during fine pulverization. Furthermore, if necessary, the toner particles and external additives can be mixed using a mixer such as a Henschel mixer to obtain a toner.
[0071] Examples of mixers include the following: Henschel Mixer (manufactured by Mitsui Mining Co., Ltd.), Super Mixer (manufactured by Kawata Co., Ltd.), Ribocone (manufactured by Okawara Manufacturing Co., Ltd.), Nauta Mixer, Turbulizer, Cyclomix (manufactured by Hosokawa Micron Corporation), Spiral Pin Mixer (manufactured by Pacific Machinery Co., Ltd.), and Loedige Mixer (manufactured by Matsubo Co., Ltd.). Examples of kneading machines include the following: KRC kneader (Kurimoto Iron Works); Buss-Co kneader (Buss); TEM type extruder (Toshiba Machine); TEX twin-screw kneader (Japan Steel Works); PCM kneader (Ikegai Iron Works); three-roll mill, mixing roll mill, kneader (Inoue Seisakusho); Kneadex (Mitsui Mining); MS-type pressure kneader, Niderruder (Moriyama Seisakusho); Banbury mixer (Kobe Steel, Ltd.).
[0072] Examples of pulverizers include the following: Counter Jet Mill, Micron Jet, Innomizer (manufactured by Hosokawa Micron Corporation); IDS type mill, PJM jet pulverizer (manufactured by Nippon Pneumatic Mfg. Co., Ltd.); Cross Jet Mill (manufactured by Kurimoto Iron Works Co., Ltd.); Urmax (manufactured by Nisso Engineering Co., Ltd.); SK Jet-O-Mill (manufactured by Seishin Enterprise Co., Ltd.); Cryptron (manufactured by Kawasaki Heavy Industries, Ltd.); Turbo Mill (manufactured by Turbo Industrial Co., Ltd.); Super Rotor (manufactured by Nisshin Engineering Co., Ltd.). If necessary, after pulverization, the toner particles may be subjected to a surface treatment using the following devices to control the average circularity of the toner particles: Hybridization System (manufactured by Nara Machinery Works), Nobilta (manufactured by Hosokawa Micron Corporation), Mechanofusion System (manufactured by Hosokawa Micron Corporation), Faculty (manufactured by Hosokawa Micron Corporation), Innomizer (manufactured by Hosokawa Micron Corporation), Theta Composer (manufactured by Tokuju Manufacturing Co., Ltd.), Mechano Mill (manufactured by Okada Seiko Co., Ltd.), Meteor Rainbow MR Type (manufactured by Nippon Pneumatic Co., Ltd.).
[0073] Examples of classifiers include the following: Classeal, Micron Classifier, and Spedic Classifier (manufactured by Seishin Enterprise Co., Ltd.); Turbo Classifier (manufactured by Nisshin Engineering Co., Ltd.); Micron Separator, Turboplex (ATP), and TSP Separator (manufactured by Hosokawa Micron Corporation); Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), Dispersion Separator (manufactured by Nippon Pneumatic Industry Co., Ltd.); and YM Microcut (manufactured by Yaskawa Shoji Co., Ltd.).
[0074] Examples of sieving devices used to sift out coarse particles include the following: Ultrasonic (manufactured by Koei Sangyo Co., Ltd.); Resonaseave, Gyroshifter (manufactured by Tokuju Kogyo Co., Ltd.); Vibrasonic System (manufactured by Dalton Co., Ltd.); Soniclean (manufactured by Shinto Kogyo Co., Ltd.); Turbo Screener (manufactured by Turbo Industry Co., Ltd.); Microshifter (manufactured by Makino Sangyo Co., Ltd.); and circular vibrating sieve.
[0075] <Method of measuring the particle size distribution of toner particles> Next, a method for measuring the particle size distribution of toner particles according to the present disclosure will be described. A precision particle size distribution measuring device using the pore electrical resistance method (product name: Coulter Counter Multisizer 3) and dedicated software (product name: Beckman Coulter Multisizer 3 Version 3.51, manufactured by Beckman Coulter, Inc.) are used. An aperture diameter of 100 μm is used, and measurements are made with an effective number of measurement channels of 25,000. The measurement data is then analyzed and calculations are made. The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass, for example ISOTON II (trade name) manufactured by Beckman Coulter, Inc. Before carrying out the measurement and analysis, the dedicated software is set up as follows.
[0076] In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement. In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range from 2 μm to 60 μm.
[0077] The specific measurement method is as follows. (1) Pour about 200 mL of the electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "aperture flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) Approximately 30 mL of the aqueous electrolyte solution is placed in a 100 mL flat-bottom glass beaker, and approximately 0.3 mL of a dilution obtained by diluting the below-mentioned "Contaminon N" three times by mass with ion-exchanged water is added thereto as a dispersant. Contaminon N: A 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.
[0078] (3) A specified amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 mL of the above-mentioned Contaminon N is added to this water tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized.
[0079] (5) In a state where the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner particles are added little by little to the electrolyte solution and dispersed. Then, the ultrasonic dispersion process is continued for another 60 seconds. During the ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C to 40°C. (6) The (5) electrolyte solution in which the toner particles are dispersed is dropped into the (1) round-bottom beaker placed in the sample stand using a pipette to adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight-average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume%, the "Average diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight-average particle size (D4). EXAMPLES
[0080] The basic configuration and features of the present disclosure have been described above, and the present invention will be specifically described below based on examples. However, the present disclosure is not limited to these. Note that parts and % are based on mass unless otherwise specified.
[0081] <Production example of binder resin 1> Bisphenol A ethylene oxide (2.2 mole adduct): 50.0 mole parts Bisphenol A propylene oxide (2.2 mole adduct): 50.0 mole parts Terephthalic acid: 90.0 parts by mole Trimellitic anhydride: 10.0 mol parts
[0082] 100 parts by mass of the monomer constituting the polyester unit was mixed together with 500 ppm of titanium tetrabutoxide in a 5-liter autoclave. A reflux condenser, a moisture separator, an N2 gas inlet tube, a thermometer, and a stirrer were attached to the autoclave, and a condensation polymerization reaction was carried out at 230°C while introducing N2 gas into the autoclave. The reaction time was adjusted to obtain a desired softening point, and after the reaction was completed, the mixture was removed from the vessel, cooled, and pulverized to obtain binder resin 1 containing 100% by mass of an amorphous polyester resin. As shown in Table 1A, the Tm of binder resin 1 was 130°C, and the Tg was 57°C.
[0083] <Production example of binder resin 2> Bisphenol A ethylene oxide (2.2 mole adduct): 50.0 mole parts Bisphenol A propylene oxide (2.2 mole adduct): 50.0 mole parts Terephthalic acid: 65.0 parts by mole Trimellitic anhydride: 25.0 mol parts Acrylic acid: 10.0 mol parts
[0084] 70 parts of the mixture of monomers for forming the polyester resin was charged into a four-neck flask, which was equipped with a pressure reducing device, a water separating device, a nitrogen gas introducing device, a temperature measuring device and a stirring device, and stirred at 160° C. in a nitrogen atmosphere. 30 parts of vinyl monomers (90.0 mol parts of styrene and 10.0 mol parts of 2-ethylhexyl acrylate) for producing a vinyl resin and 1 part of benzoyl peroxide as a polymerization initiator were added dropwise from a dropping funnel over a period of 4 hours, and the mixture was allowed to react at a temperature of 160°C for 5 hours. Thereafter, the temperature was raised to 230°C, and 0.2 parts of titanium tetrabutoxide based on the total amount of monomers forming the polyester resin was added, and polymerization was carried out until Tm reached 130°C. After the reaction was completed, the mixture was taken out of the vessel, cooled and pulverized to obtain Binder Resin 2. As shown in Table 1A, Tg was 55°C.
[0085] <Production Example of Binder Resin 3> Binder resin 3 was obtained in the same manner as binder resin 2, except that the mixture of monomers forming a polyester resin was changed to 50 parts and the vinyl monomers forming a vinyl resin were changed to 50 parts. As shown in Table 1A, Tm was 135°C and Tg was 56°C. <Production example of binder resin 4> Binder resin 4 was obtained in the same manner as binder resin 2, except that the mixture of monomers forming a polyester resin was changed to 25 parts and the vinyl monomers forming a vinyl resin were changed to 75 parts. As shown in Table 1A, Tm was 130°C and Tg was 53°C.
[0086] <Production Example of Styrene-Acrylic Resin Composition 1> In an autoclave reactor equipped with a thermometer and a stirrer, 300.0 parts of xylene and 15.0 parts of polypropylene were placed and thoroughly dissolved, and the atmosphere was replaced with nitrogen. Then, a mixed solution of 69.0 parts of styrene, 4.5 parts of cyclohexyl methacrylate, 3.5 parts of methacrylic acid, 8.0 parts of behenyl acrylate, and 250.0 parts of xylene was dropped at a temperature of 180°C for 3 hours to polymerize. The mixture was further kept at this temperature for 30 minutes, and the solvent was removed to obtain a styrene-acrylic resin composition 1. The ATR index (B / A), acid value, and weight average molecular weight of the obtained styrene-acrylic resin composition are shown in Table 1B.
[0087] <Production Examples of Styrene-Acrylic Resin Compositions 2 to 12> Styrene acrylic resin compositions 2 to 12 were obtained in the same manner as styrene acrylic resin composition 1, except that the type of hydrocarbon compound, its amount, etc. were changed as shown in Table 1B. The ATR index (B / A), acid value, and weight average molecular weight of the obtained styrene acrylic resin compositions are shown in Table 1B.
[0088] [Table 1A]
[0089] [Table 1B]
[0090] <Example 1> (Toner 1 manufacturing example) Binding resin 1 100 parts Fischer-Tropsch wax (melting point 90°C) 7 parts Styrene-acrylic resin composition 1 8.4 parts CI Pigment Blue 15:3 4 parts The above materials were premixed in a Henschel mixer, and then melt-kneaded at 160° C. in a twin-screw kneading extruder.
[0091] The resulting kneaded product was cooled, coarsely pulverized in a hammer mill, and then finely pulverized in a turbo mill. The resulting finely pulverized product was classified using a multi-division classifier utilizing the Coanda effect, to obtain toner particles 1 having a weight average particle size (D4) of 6.0 μm. For 100 parts of the toner particles, hydrophobically treated silica fine particles (with a specific surface area of 140 m2 measured by nitrogen adsorption using the BET method) were 2 The mixture was sieved through a mesh having an opening of 150 μm to obtain toner 1.
[0092] The toner 1 and the magnetic carrier were mixed in a V-type mixer (product name: V-10 type, Tokuju Manufacturing Co., Ltd.) for 0.5 seconds so that the toner concentration became 7% by mass. -1 The mixing was performed under the conditions of a rotation time of 5 minutes. The magnetic carrier used was magnetic ferrite carrier particles (number average particle size: 35 μm) whose surfaces were coated with acrylic resin. In this manner, a two-component developer 1 was obtained. Using two-component developer 1, the evaluation described below was carried out.
[0093] The image forming apparatus used was a modified Canon imageRUNNER ADVANCE C9075 PRO digital commercial printing printer, with two-component developer 1 placed in the cyan developer. The developer carrier's DC voltage VDC, electrostatic latent image carrier's charging voltage VD, and laser power were adjusted so that the amount of toner carried on the electrostatic latent image carrier or paper was as desired, and the evaluation described below was performed. Modifications included making it possible to freely set the fixing temperature and process speed.
[0094] (Abrasion resistance) Paper: OK Topcoat + (128.0g / m 2 ) Evaluation image: 10cm where the reflection density is 0.15 2 Halftone image Fixing test environment: Normal temperature and humidity environment (temperature 23°C / relative humidity 50%) Process speed: 350mm / sec Using the above image forming apparatus, a halftone image was output under the above conditions. The abrasion resistance was evaluated by the following method. First, apply 0.2kgf / cm to the part where the halftone image is printed. 2 The fixed image was rubbed (10 times back and forth) with the above-mentioned white coated paper while applying a load of 1000 mm. The average reflectance Ds (%) of the white background of the coated paper was measured using a reflectometer (REFLECTOMETER MODEL TC-6DS, manufactured by Tokyo Denshoku Co., Ltd.). Next, the average reflectance Dr (%) of the rubbed portion of the coated paper used for rubbing was measured. Then, the fog (%) was calculated using the following formula. The obtained fog was evaluated according to the following evaluation criteria. Fog(%)=Dr(%)-Ds(%)
[0095] (Evaluation Criteria) A: Less than 2.0% B: 2.0% or more, less than 5.0% C: 5.0% or more, less than 10.0% D: 10.0% or more, less than 15.0% E: 15.0% or more
[0096] (Hot offset resistance) Evaluation paper: A4 paper CS-680 (68.0g / m 2 ) (Sold by Canon Marketing Japan Inc.) Toner amount on evaluation paper: 0.08mg / cm 2 Evaluation image: A halftone image (2cm x 2cm) placed in the center of the A4 paper. Fixing test environment: Normal temperature and low humidity environment: Temperature 23°C / Relative humidity 5% (hereinafter referred to as "N / L") Process speed: 321mm / sec Fixing temperature: 200℃
[0097] The above evaluation image (unfixed image) was prepared. Next, 10 blank postcards (normal postcards with blank backs, 100 mm×148 mm in size, sold by Japan Post Co., Ltd.) were passed through the center of the fixing belt, and then one evaluation paper with the above unfixed image was passed through and fixed. Then, the average reflectance Dr (%) of the evaluation paper before image output and the reflectance Ds (%) of the white background after the fixing test were measured using a reflectometer (REFLECTOMETER MODEL TC-6DS: manufactured by Tokyo Denshoku), and the fogging was calculated using the following formula. The obtained fogging was evaluated according to the following evaluation criteria. Fog(%)=Dr(%)-Ds(%)
[0098] (Evaluation Criteria) A: Less than 0.2% B: 0.2% or more, less than 0.5% C: 0.5% or more, less than 1.0% D: 1.0% or more
[0099] (Charge retention) In a high temperature and humidity environment (temperature 32.5°C, relative humidity 80%), the amount of toner carried on the electrostatic latent image carrier is 0.35 mg / cm 2The toner particles were collected by suction using a metal cylindrical tube and a cylindrical filter. The charge amount Q stored in the capacitor through the metal cylindrical tube and the mass M of the collected toner were measured, and the charge amount per unit mass Q / M (mC / kg) was calculated and used as the charge amount Q / M (mC / kg) on the electrostatic latent image carrier. After carrying out the above evaluations, the developing unit was removed from the machine and left to stand for 72 hours in an environment of a temperature of 32.5°C and a relative humidity of 80%, and then the developing unit was reinserted into the machine and the charge amount Q / M per unit mass on the electrostatic latent image carrier was measured at the same DC voltage VDC as in the initial evaluation. The initial Q / M on the electrostatic latent image carrier was set at 100%, and the retention rate of Q / M on the photoreceptor after standing for 72 hours ([Q / M after standing for 72 hours] / [initial Q / M] x 100) was calculated and evaluated according to the following criteria.
[0100] (Evaluation Criteria) A: Retention rate is over 80% B: Retention rate is between 70% and 80% C: Retention rate is between 60% and 70% D: Retention rate is less than 60% Two-component developer 1 was rated A for abrasion resistance, hot offset resistance, and charge retention.
[0101] <Examples 2 to 9 and Comparative Examples 1 to 4> (Toner 2 to 13 manufacturing examples) Toners 2 to 13 were obtained in the same manner as in the production example of Toner 1, except that the types and amounts of the binder resin, styrene acrylic resin composition, and hydrocarbon wax were changed as shown in Table 2.
[0102] [Table 2] PES ratio=(P / (P+V))×100(%) P: Total amount of monomers that produce polyester resin (parts by mass) V: Total amount of monomers that produce vinyl resin (parts by mass)
[0103] (Production Examples of Developers 2 to 13) Developers 2 to 13 were obtained in the same manner as in the production example of developer 1, except that the toner was changed as shown in Table 3. Furthermore, evaluation was performed in the same manner as for developer 1. The evaluation results are shown in Table 3.
[0104] [Table 3]
[0105] For developers 1 to 13, the evaluation image for the abrasion resistance evaluation conditions in a normal temperature and humidity environment (temperature 23°C / relative humidity 50%) was changed to a solid image, and the reflection density was measured, resulting in a value of 1.40 or more for all of them. The reflection density was measured using a spectrodensitometer 500 series (manufactured by X-Rite Corporation), and five arbitrary points on the first, fifth, and tenth images of ten solid images were measured and the average value was calculated.
Claims
1. A toner having toner particles containing a binder resin, a hydrocarbon wax, and a styrene-acrylic resin composition, The binder resin contains 30% by mass or more of an amorphous polyester resin, The styrene-acrylic resin composition contains 4% by mass to 25% by mass of a unit represented by the following formula (1): The styrene-acrylic resin composition has an FT-IR spectrum measured by an ATR method under conditions of Ge as an ATR crystal and an infrared light incidence angle of 45°, in which the 1570 cm -1 ~1630cm -1 The maximum absorption peak intensity in the range of A is 2800 cm due to the C-H bond of the hydrocarbon. -1 ~2900cm -1 When the maximum absorption peak intensity in the range is B, the ratio of B to A (B / A) is 1.8 to 4.0; The toner is characterized in that it contains 3 to 15 parts by mass of the hydrocarbon wax per 100 parts by mass of the binder resin. 【Chemistry 1】 (In formula (1), n is an integer of 10 to 36, and R is H or CH 3 Indicates.)
2. The toner according to claim 1, wherein the styrene-acrylic resin composition is a graft polymer having a hydrocarbon compound as a backbone portion and a styrene-acrylic resin as a branch portion.
3. The toner according to claim 2, wherein the hydrocarbon compound is a polyolefin.
4. A toner described in any one of claims 1 to 3, wherein the binder resin contains 50 mass% or more of an amorphous polyester resin.
5. The toner described in any one of claims 1 to 4, wherein the styrene acrylic resin composition contains 10% by mass to 30% by mass of a hydrocarbon compound unit.
6. The toner described in any one of claims 1 to 5, wherein the styrene-acrylic resin composition contains 50 mass% or more of styrene units.
7. The toner according to any one of claims 1 to 6, wherein when the content of the styrene acrylic resin composition in the toner is X (mass%) and the content of the hydrocarbon wax in the toner is Y (mass%), a ratio of X to Y (X / Y) is 0.8 to 1.
5.
8. The toner according to claim 1, wherein the acid value of the styrene-acrylic resin composition is 10.0 mg KOH / g to 30.0 mg KOH / g.
9. The weight average molecular weight of the styrene-acrylic resin composition is 1.5 × 10 4 ~1.0 x 10 5 9. The toner according to claim 1, wherein
Citation Information
Patent Citations
Toner for binary system developer
JP1996076413A
Method for producing electrostatic charge image development toner
JP2016057434A
Wax dispersant for toner and toner
JP2017045048A
Toner
JP2017116810A
Toner and manufacturing method of toner
JP2020008818A
